A geographical retheorization of the tourism value chain - Liu, Yi (ERDKUNDE, 2022)
Based on a sympathetic critique of the current research on the tourism value chain, this paper finds certain ambiguities in the understanding of the theoretical context of the value chain literature, and there is inadequate attention towards the role of geography. This paper reveals how the ambiguities are created and why geography is important. In order to reduce the ambiguities of the tourism value chain, the spatiality of tourism value chain is theorized concerning spatial stickiness and experiential value of tourism resources. This paper thus argues that the tourism value chain is subject to a carrier-driven pattern of governance rather than producer or buyer-driven. This endeavour helps us better understand the general mechanism of value creation and distribution in the tourism industry rather than taking it for granted that it is the same as in the manufacturing industries.